Auditing: Integrated Concepts and Procedures (Book). - Engle, Terry J.; Hendrickson, Harvey S. (The Accounting Review, 1986)
Reviews the book "Auditing: Integrated Concepts and Procedures," 3rd ed., by Donald H. Taylor and G. William Glezen.